2013
DOI: 10.1016/j.fishres.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Growth estimates of cardinalfish (Epigonus crassicaudus) based on scale mixtures of skew-normal distributions

Abstract: Our article presents a robust and flexible statistical modeling for the growth curve associated to the age-length relationship of Cardinalfish (Epigonus Crassicaudus). Specifically, we consider a non-linear regression model, in which the error distribution allows heteroscedasticity and belongs to the family of scale mixture of the skewnormal (SMSN) distributions, thus eliminating the need to transform the dependent variable into many data sets. The SMSN is a tractable and flexible class of asymmetric heavy-tai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Currently, only basic knowledge for cardinalfish on growth (Gálvez et al., ; Cubillos et al., ; Ojeda et al., ; Contreras‐Reyes and Arellano‐Valle, ), natural mortality (Cubillos et al., ; Tascheri et al., ) and maturity (Gálvez et al., ; Cubillos et al., ) is available. Gálvez et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, only basic knowledge for cardinalfish on growth (Gálvez et al., ; Cubillos et al., ; Ojeda et al., ; Contreras‐Reyes and Arellano‐Valle, ), natural mortality (Cubillos et al., ; Tascheri et al., ) and maturity (Gálvez et al., ; Cubillos et al., ) is available. Gálvez et al.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, only basic knowledge for cardinalfish on growth (G alvez et al, 2000;Cubillos et al, 2009;Ojeda et al, 2010;Contreras-Reyes and Arellano-Valle, 2013), natural mortality (Cubillos et al, 2009;Tascheri et al, 2012) and maturity (G alvez et al, 2000;Cubillos et al, 2009) is available. G alvez et al (2000) and Cubillos et al (2009) reported on maturity ogives in this species; both reproductive studies showed significant differences between estimates of length at 50% of maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this study we assumed multiplicative log‐normal errors in order to describe the uncertainty not captured by VBGF. This provides several advantages, such as the interpretations of li and reduced standard errors (Quintero, Contreras‐Reyes, Wiff, & Arellano‐Valle, ), however other, more flexible, error distributions that have been proposed, such as the log‐skewed‐t distribution (e.g., Contreras‐Reyes & Arellano‐Valle, ). Furthermore, we plan to investigate whether fish spawned in the same time period (e.g., year) have similar growth patterns in order to try and explain some of the uncertainty not captured in our model.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters of the von Mises distributions in models IV and V were taken from Datta & Blanchard (). In models III and V, f(·) was defined in equation , with m=3, x2=0.75, and ffalse(0.75false)=c2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation